Pendidikan Iman bagi Kaum Muda Menurut Paus Fransiskus dalam Seruan Apostolik Evangelii Gaudium - Gautama, Moses Putra; Adrian, Vincentius Paskalis Felix; Mulyatno, C.B. (Proceedings of The National Conference on Indonesian Philosophy and Theology, 2025)
Young people are essential members of the Church who play a significant role in proclaiming the Good News in both the present and the future. As they are in direct contact with the advancements of today's world, young people need to be equipped with a strong foundation of faith. Pope Francis, in his apostolic exhortation Evangelii Gaudium, provides special attention to the education of the youth. This article aims to identify and describe faith education for young people according to Pope Francis in Evangelii Gaudium. In this research, the author employs the library research method to explore the content of Evangelii Gaudium. The results of this study show that Evangelii Gaudium offers a call to proclaim the Gospel in the modern era to all members of the Church. Therefore, young people must receive adequate education to become evangelizers. The elements of faith education for Catholic youth include the model of faith education, the parties involved, the objectives, the subject matter, the content of faith education, and the strategies for faith education.AbstrakKaum muda merupakan anggota Gereja yang berperan penting dalam pewartaan kabar gembira di masa sekarang dan masa depan. Kaum muda yang bersentuhan langsung dengan kemajuan dunia saat ini perlu memiliki bekal hidup beriman yang kokoh. Paus Fransiskus, dalam seruan apostolik Evangelii Gaudium, memberikan beberapa perhatian khusus bagi pendidikan kaum muda. Penulisan artikel ini bertujuan untuk mengidentifikasi dan mendeskripsikan pendidikan iman bagi kaum muda menurut Paus Fransiskus dalam Evangelii Gaudium. Dalam penelitian ini, penulis menggunakan metode studi pustaka (library research) untuk mengeksplorasi isi Evangelii Gaudium. Hasil dari penelitian ini menunjukkan bahwa Evangelii Gaudium memberikan suatu dorongan bagi pewartaan Injil di zaman modern ini bagi seluruh lapisan umat di dalam Gereja. Untuk itu, kaum muda perlu mendapatkan bekal pendidikan yang memadai untuk menjadi pewarta. Unsur-unsur pendidikan iman bagi kaum muda Katolik berupa model pendidikan iman, pihak-pihak yang berperan dalam pendidikan iman, tujuan pendidikan iman, objek pendidikan iman, isi pendidikan iman, dan strategi pendidikan iman.